Peningkatan Visibilitas Digital Produk Pupuk Hayati pada PT. Manunggal Merdeka Makmur - Anindhyta Budiarti; Rahma Wahyu Idayani; Achmad Fakhri Dzulfiqar; Zhivora Amelia Haq; Anang Subardjo; Soraya Nur Hasana; Adam Dwi Isnaini (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program (PKM) aims to enhance the digital visibility of PT. Manunggal Merdeka Makmur, a biofertilizer manufacturing company in Nganjuk, East Java, Indonesia. Prior to this program, the company lacked an official digital presence to effectively promote its product to broader markets. The program employed Design Science Research (DSR) methodology combined with a participatory approach, encompassing socialization, training, technology implementation, mentoring, and evaluation stages. Results demonstrate that an e-company profile website was successfully developed and deployed at manunggalmerdekamakmur.com, providing the company an official digital identity and online product information platform. Additionally, company human resources received training in digital marketing and website content management. The program contributes to the digital transformation of fertilizer SMEs and confirms that integrated digital media development combined with human resource capacity building effectively enhances market reach and competitive advantage.